2022
DOI: 10.3389/fevo.2022.825689
|View full text |Cite
|
Sign up to set email alerts
|

Less Is More: Lowering Cattle Stocking Rates Enhances Wild Herbivore Habitat Use and Cattle Foraging Efficiency

Abstract: Over a quarter of the world’s land surface is grazed by cattle and other livestock, which are replacing wild herbivores and widely regarded as drivers of global biodiversity declines. The effects of livestock presence versus absence on wild herbivores are well documented. However, the environmental context-specific effects of cattle stocking rate on biodiversity and livestock production are poorly understood, precluding nuanced rangeland management recommendations. To address this, we used a long term exclosur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
(102 reference statements)
0
10
0
Order By: Relevance
“…Further research on water availability and livestock density may benefit from a specific focus. For example, wildebeest cannot survive without water for more than 2-3 days (Talbot and Talbot, 1963) and domestic livestock compete with wild herbivores for grazing resources (Schieltz and Rubenstein, 2016;Kimuyu et al, 2017;Crego et al, 2020;Connolly et al, 2021;Wells et al, 2022). However, data were not available at an appropriate spatio-temporal resolution to be included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Further research on water availability and livestock density may benefit from a specific focus. For example, wildebeest cannot survive without water for more than 2-3 days (Talbot and Talbot, 1963) and domestic livestock compete with wild herbivores for grazing resources (Schieltz and Rubenstein, 2016;Kimuyu et al, 2017;Crego et al, 2020;Connolly et al, 2021;Wells et al, 2022). However, data were not available at an appropriate spatio-temporal resolution to be included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In central Kenya, it has been suggested that Opuntia have expanded as a consequence of overgrazing by livestock, which creates microsites suitable for establishment (Strum et al, 2015). However, our findings suggest the hypothesis that indirect facilitation of Opuntia by livestock may be mediated more by the suppression of wild herbivores that tends to accompany livestock production (Crego et al, 2020; Wells, Crego, Ekadeli, et al, 2022) than by the reduction of competition with native understory plants. It may be that cactus establishment is hampered by competition with understory vegetation in herbivore exclosures during the early stages of invasion (as observed in a related species, O. fragilis ; Burger & Louda, 1994), but that this effect is later overshadowed by herbivore‐induced suppression (Levine et al, 2004).…”
Section: Discussionmentioning
confidence: 59%
“…The overstocking of pasture with cattle in these areas is detrimental to wild herbivores. However, lower stocking rates with cattle may represent a win–win for wild herbivore conversation and the individual performance of livestock [ 85 ]. Further research and innovation from local ranchers are required to develop sustainable grazing that can co-exist with wildlife.…”
Section: Grazing In Africamentioning
confidence: 99%